MENINGKATKAN KOLABORASI TIM MELALUI PENGEMBANGAN ORGANISASI YANG BERFOKUS PADA KESEJAHTERAAN KARYAWAN - Aisatul Hasanah; Hesti Anggraeni Soleha; Sulistiasih (Jurnal Ekonomi dan Bisnis, 2024)
Employee welfare has a large role in organizational development in the current era by increasing collaboration between team members. The aim of this research is to provide insight into organizational development in team member collaboration regarding employee welfare. The method used in this research is a qualitative method using literature study. This research collects data by reviewing books, scientific journals and other literature that is relevant and reliable to the research subject. The research results show that organizational development to achieve common goals requires employee involvement in increasing team member collaboration. Meanwhile, increasing eflective collaboration will have a positive impact on employees' psychological well-being. So in organizational development, every employee needs training to train their abilities and skills. Apart from that, eflective communication and respect for mutual opinions in resolving problems within the organization between fellow employees to achieve common goals is very necessary in increasing team member collaboration.